Fasilitasi Pembelajaran Daring Berbasis 4C (Critical Thinking, Creatifity, Collaboration and Comunication) di MI Ma’arif Kebondalem Wonosobo - Adi Suwondo; Robingun Suyud El-Syam; Ahmad Guspul (Universitas Pendidikan Indonesia Kampus Serang, 2022)
The use of information and communication technology in the learning process is one of the pedagogical competencies that must be possessed by an educator and education staff. In reality, many of them are not yet able to use ICT for learning, so assistance is needed for them. Through 5 mentoring strategies including delivering the benefits of Google Classroom, feature introduction, usage practice, one-on-one mentoring, and presentation of results, educators and education staff at MI Ma’arif Kebondalem Wonosobo can practice 4C-based online learning (Critical thinking, Creativity, Collaboration and Communication). With the Google Classroom. The purpose of community service is so that teachers understand how to use google classroom to improve the quality of student learning. A survey conducted on the ICT quality of Madrasah Ibtidaiyah teachers found that teacher competence in ICT was very low in the ability to use and utilize applications, which was 52%. Furthermore, a very low indicator is found in the experience aspect of participating in training at 57%. Through Google Classroom, an internet-based service provided developed by Google for e-learning activities, teachers feel making it easier for teachers to manage classes, and improve communication with students without using paper. This assistance to teachers is considered successful in solving teacher competence problems at MI Ma’arif Kebondalem Wonosobo.